PELAKSANAAN BELAJAR DARI RUMAH (BDR) DI SMK NEGERI 1 BANYUDONO (Studi Kasus pada Kelas X) - Dyah Ayu Siswiyanti; Hery Sawiji; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
This study aims to determine: 1) The application of BDR at SMK Negeri 1 Banyudono,2) The obstacles in the implementation of BDR at SMK Negeri 1 Banyudono,3) Strategic efforts in overcoming obstacles to BDR at SMK Negeri 1 Banyudono. This type of research is descriptive qualitative using a case study approach. The validity of the data was obtained by triangulation of techniques and sources. The data analysis technique uses an interactive model. The research procedure are as follows: 1) Problem identification,2) Research focus determination,3) Data collection,4) Data analysis, and 5) Research results reporting. The results of the study show that: 1) The BDR process at SMK Negeri 1 Banyudono includes: a) planning begins with the provision of workshops and the preparation of learning administration,b) Implementation using WhatsApp Group, Google Meet, and Google Classroom media, c)Monitoring is carried out through Google Classroom and Office 365 media, d)Evaluation activities are carried out during the morning apple activity.2) The Implementation of BDR has obstacles including: a) Students do not have internet quotas and unstable networks,b) Students find it difficult to concentrate,c) Limited use of learning media and 3) Strategic efforts in dealing with obstacles include: a) Providing assistance quotas and allowances for students,b) Handling of Guidance and Counseling Teachers, c)Provision of Training and Socialization.